The Role of Polypyrimidine Tract-Binding Proteins and Other hnRNP Proteins in Plant Splicing Regulation - Wachter, Andreas; Rühl, Christina; Stauffer, Eva (Frontiers in Plant Science, 2012)
Alternative precursor mRNA splicing is a widespread phenomenon in multicellular eukaryotes and represents a major means for functional expansion of the transcriptome. While several recent studies have revealed an important link between splicing regulation and fundamental biological processes in plants, many important aspects, such as the underlying splicing regulatory mechanisms, are so far not well understood. Splicing decisions are in general based on a splicing code that is determined by the dynamic interplay of splicing–controlling factors and cis-regulatory elements. Several members of the group of heterogeneous nuclear ribonucleoprotein (hnRNP) proteins are well known regulators of splicing in animals and the comparatively few reports on some of their plant homologs revealed similar functions. This also applies to polypyrimidine tract-binding proteins, a thoroughly investigated class of hnRNP proteins with splicing regulatory functions in both animals and plants. Further examples from plants are auto- and cross-regulatory splicing circuits of glycine-rich RNA binding proteins and splicing enhancement by oligouridylate binding proteins. Besides their role in defining splice site choice, hnRNP proteins are also involved in multiple other steps of nucleic acid metabolism, highlighting the functional versatility of this group of proteins in higher eukaryotes.